Does A Block Holder's Power Over Tax Avoidance Increase With Political Connections? - Kartikasari, Dwiyana (Educoretax, 2024)
Tax Avoidance cannot be separated from business management planning and statutory regulations which still have room for abuse. In practice, the interests of taxpayers and the state differ. Taxpayers try to pay as little tax as possible, because paying taxes weakens the economic function of taxes. On the other hand, the government needs funds to finance government administration, most of which comes from tax revenues. These differences in interests force taxpayers to reduce the amount of their tax payments, both legally and illegally. This research aims to analyze the direct impact of political block, blockholders consisting of families, institutions, countries and foreign controllers on tax avoidance. This research uses the causality method. The sample used was 109 company groups in 2018-2022 (1,090 panel data). Data analysis uses moderated regression analysis (MRA). Political connections and blockholders consisting of families and institutions have a significant influence on tax avoidance. Political connections moderate the influence of controlling shareholder families on tax avoidance at the 10-50% ownership limit. This shows that companies that have political connections and are controlled by families tend to avoid taxes. The results of this research support the resource dependency theory where political connections are used by companies as a resource in carrying out tax avoidance and as a way to lighten the tax burden, especially for companies controlled by families. This research is limited to a sample group without identifying the company's business strategy, whether related to diversification or unrelated diversification.